Think Tank networks of German neoliberalism. Power structures in economics and economic policies in post-war Germany - Stephan Pühringer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
Even after the financial crisis, economists still exert influence on politics and society in general on several levels and thus can be still interpreted as a discipline of power. Particularly in Germany there is a long tradition of institutionalized economic policy advice, which offers economists a channel of direct and indirect impact on politics. During the European crisis policies many scholar stressed a "comeback", "revival" or "return" of ordoliberalism, the German variety of neoliberalism. In this paper I show how economists connected in the "German neoliberal thought collective" since the end of WW II have built up a strong institutional powerstructure, which had a continuous impact on German economic politics over many decades. It can be shown that in several turning points of German economic history, German neoliberalism and its core politico-economic concept of "Social market economy" served as guiding principle of economic policy. Furthermore I will show that up to now there is an uneven power balance among economists with high political and societal influence, i.e. economists connected in Keynesian or union-linked networks are in a minority position compared to the dense network of economists in the "German neoliberale thought collective". Hence, what was observed during the European crisis policies as a "comeback of ordoliberalism" should rather be interpreted as the consequence of a persistant influence of German neoliberal networks on German economic politics over many decades.
Keywords: 330